Enhanced hole carrier transport due to increased intermolecular contacts in small molecule based field effect transistors - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Das, Chayanika; Muddellu, Pooja; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2013)
Small molecules and oligomers can be synthesized with very high purity and precise molecular weights, but they often do not form uniform thin films while processed from solution. Decreased intermolecular contacts between the small molecules are another disadvantage. To increase the intermolecular contacts in small molecules, we have chosen i-indigo, as one of the conjugated molecular units. The electron poor i-indigo has been connected with electron rich triphenylamine to synthesize a donor-acceptor-donor type small molecule. The propeller shaped triphenylamine helps to increase the solubility of the small molecule as well as isotropic charge transport. The intermolecular spacing between the molecules has been found to be low and did not vary as a function of thermal annealing. This implies that the intermolecular contacts between the small molecules are enhanced, and they do not vary as a function of thermal annealing. Organic field effect transistors (OFET) fabricated using a small molecule exhibited a hole carrier mobility (mu) of 0.3 cm(2)/(V s) before thermal annealing. A marginal increase in mu was observed upon thermal annealing at 150 degrees C, which has been attributed to changes in thin film morphology. The morphology of the thin films plays an important role in charge transport in addition to the intermolecular spacing that can be modulated with a judicious choice of the conjugated molecular unit.
Keywords: hole mobility; i-indigo; organic field effect transistor; quadrupole interaction; small molecules; triphenylamine

Long cycling stability imparted to li-ion batteries by conjugated polymers with low dihedral angles and high electron density on functional groups - Kargude, Radhakisan; Srinivasalu, Hari Haran; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam (ACS Applied Polymer Materials, 2025)
In conjugated polymers, dihedral angles at bonds connecting their monomers impact the polymers' properties such as the packing of the polymer chains, bandgap, and conductivity. These properties are expected to impact the performance of rechargeable Li-ion batteries because the Li-ion transport and conductivity of the polymers are two important parameters. To understand this, we designed and synthesized two polymers with two different dihedral angles. The polymer, Poly(EDOT-DPP), comprising diketopyrrolopyrrole (DPP) and ethylenedioxythiophene (EDOT) as monomers, showed a low dihedral angle of 2 degrees. On the other hand, the polymer, Poly(EDOT-i-Ind), comprising EDOT and i-Indigo (i-Ind) showed a dihedral angle of 17 degrees. Density functional theory (DFT) studies showed that the electron density at the carbonyl moiety of EDOT-DPP is higher than that of EDOT-i-Ind. This resulted in a higher Li+ binding energy of -3.665 eV for EDOT-DPP and a lower Li+ binding energy of -3.464 eV for EDOT-i-Ind. Battery electrodes were fabricated using either Poly(EDOT-DPP) or Poly(EDOT-i-Ind) with multiwalled carbon nanotubes as conducting fillers in the absence of any binders. The Li+ ion diffusion coefficient ( D Li + ) measured for the as prepared batteries based on Poly(EDOT-DPP) was found to be 3.9 x 10-19 cm2/s, which is slightly higher than that found for Poly(EDOT-i-Ind). However, after 2000 cycles, the D Li + increased by about two orders of magnitude for both polymers. Due to the low dihedral angle in the case of Poly(EDOT-DPP), the D Li + was found to be 21% higher than that of Poly(EDOT-i-Ind). The higher binding of Li+ ions with Poly(EDOT-DPP) and Li+ ion diffusion improved the specific capacity and cycling performance of batteries fabricated with this polymer. At a current density of 0.2 A/g, Poly(EDOT-DPP) showed a 39% higher specific capacity than the Poly(EDOT-i-Ind) polymer after 2000 cycles. The batteries also showed stable performance over 2000 cycles with an insignificant decrease in specific capacity.
Keywords: dihedral angle; diketopyrrolopyrrole; i-indigo; Li-ion battery; Li-ion transport